(untitled) (World Science, 2022)
Biodegradation of polymers of spatial structure is complicated at the impact of soil destructive microorganisms and biodegradation requires a long time. We have implemented a target-oriented synthesis of a polymer to receive linear structure polymers where labile peptide bonds are preserved. To implement target-oriented synthesis of a polymer and to determine optimal conditions for reaction mechanism we studied the process of kinetics and its regularities – reaction temperature, duration, components ratio, concentration, reaction speed constant, and activation energy. The Arrhenius factor and succession of the introduction of initial components to the reaction medium were computed, and catalyst nature and other properties were determined. A high effect of prolongation was achieved, when carbamide and formaldehyde molar ratio were 1:1. In this case linear structure polymer is formed where peptide -CH2 – NH – are preserved.